Verktyg för värdering av miljöpåverkan vid investeringar i det svenska elstamnätet - Lövebrant, Karin (2012)
During the period 2009-2013, investments in the Swedish national grid increase by a factor of ten compared to previous years. In order to fulfil their mission to manage the national grid in a safe, efficient and environmentally sound way, Svenska Kraftnät (Swedish National Grid) needs to take all these perspectives into account while planning new investments. To compare and relate perspectives of technology, economy and environment the same yard stick must be used. That yard stick is commonly money. A problem arises however as environmental issues are difficult to price. The purpose of this master’s degree project was to develop a tool for evaluation of environmental impact related to investments in the Swedish national grid. It was initiated by and conducted at the unit for Grid development at Svenska Kraftnät. A life cycle perspective was used and the following stages were identified: material production, construction, operation and decommissioning. The environmental impact from these stages was sorted into ten impact categories using the LCIA method ReCiPe 2008 and then two economical evaluations were performed: one at midpoint level and one at endpoint level. Also included in the evaluation were the change in power losses or in the power production mix and the visual impact coming from overhead transmission lines. Impact categories Type Unit Part of economic evaluation Climate change Midpoint kg CO2 eq Midpoint evaluation Ozone depletion Midpoint kg CFC-11 eq No Particle formation Midpoint kg PM10 eq Midpoint evaluation Acidification Midpoint kg SO2 eq Midpoint evaluation Eutrophication Midpoint kg P eq Midpoint evaluation Use of metallic resources Midpoint kg Fe eq No Use of fossile resources Midpoint kg oil eq No Damage on human health Endpoint DALY Endpoint evaluation Damage on ecosystem quality Endpoint disappeared species per year Endpoint evaluation Resource depletion Endpoint $ Endpoint evaluation The tool was implemented in Excel and offers the possibility to evaluate the environmental impact from five different power line technologies (per km), substation line bays (per bay), transformers (per piece) and reactors (per piece). The main results show that AC land cable has a significantly higher environmental impact and cost than the other power line technologies. Material production and construction are the life cycle stages that contribute the most to the environmental cost. The impact categories that affect the environmental cost the most are climate change (for midpoint evaluation) and resource depletion (for endpoint evaluation). When the investment affects the power production mix, e.g. by changing the transmission capacity to another country, the subsequent environmental impact can be very influential on the total environmental cost of the investment.